(untitled) (INTERNATIONAL JOURNAL OF CONSTRUCTION ENGINEERING (IJCE), 2020)
The present work is focused on understanding the uplift capacity of vertical and inclined piles passing through two layered soil and subjected to the inclined loads. The study was carried out using finite element software MIDAS 3D. The foundation soil was modeled as an elasto-plastic material obeying the Mohr-Coulomb failure criterion. The parametric studies were performed by varying the diameter of pile, angle of inclination of load (a) and pile angle (q). It was observed that the uplift capacity of pile depends upon these parameters. The uplift capacity of pile varies with inclination of pile angle and inclination of load.